Genetic Variability and Correlation Studies in Gladiolus Hybridus Hort. Under Bundelkhand Conditions (Bangladesh Journal of Botany, 2022)
A field experiment was conducted to estimate genetic variability, heritability and correlation among the economically important characters in gladiolus varieties at the Instructional Farm, College of Horticulture, BUAT, Banda. The healthy and uniform sized corms (4 to 5 cm) were planted at a spacing of 30 × 20 cm in each row at a depth of 5-6 cm. Before planting, corms were dipped in captan (0.2%) solution for 25-30 min as a preventive measure against Fusarium wilt disease. The varieties showed significant variability (p < 0.05) for days taken to spike emergence (66.67-86.69 days), days taken to opening of first floret (86.21-101.80 days), plant height (74.93 to 105.47 cm), spike length (67.07 to 89.93 cm), rachis length (33.89 to 55.64 cm), water uptake (17.33-46.67 ml), corm weight (39.97 to 100 g) and number of cormels per plant (4.47-41.97). Phenotypic coefficient of variation and genotypic coefficient of variation were high for the traits studied, except days taken to spike emergence, days taken to opening of first floret and corm diameter. High broadsense heritability value was found for number of corms per plant (90.64 %), corm weight (76.09 %) and days taken to opening of first floret, indicating the presence of additive gene effects. Positive correlation was found between days taken to spike emergence and days taken to opening of first floret (r = 0.880**); number of leaves per plant (r = 0.543*), plant height (r = 0.560*) and corm weight (r = 0.515*).Bangladesh J. Bot. 51(4): 705-712, 2022 (December)